The Early Years Pupil Premium: practitioners' perspectives on if the funding supports 'closing the gap' for looked after children?. Issue 16 (10th December 2021) - Williams-Brown, Zeta
ABSTRACT: The paper investigates practitioners' perspectives on the Early Years Pupil Premium (EYPP) and its use for looked after children (LAC) in England. The paper considers what practitioners in one Local Authority (LA) think now that the funding has passed its infancy. Specifically, does EYPP funding help 'close the gap' for LAC? Q-methodology was used to investigate 19 practitioners' perspectives; all were owners or managers in 19 different settings. This approach was complemented with a questionnaire survey and focus groups held with 14 practitioners in 13 different settings in the same LA. The findings revealed that practitioners consistently focused on whether all LAC should be eligible for this funding and/or whether the funding is able to 'close the gap' between them and their peers. It concludes that EYPP funding can support 'closing the gap' for LAC with developmental delay, but its purpose needs to be clarified.